Development of increased epithelial permeability syndrome in rheumatological patients. - Kh.M. Marufkhanov; M.V. Sibirkina; Kh.T. Nurmetov; A.R. Gimadutdinova; J.J. Mullokulov (Genius Journals, 2022)
Currently, the role of the syndrome of increased epithelial permeability of the gastrointestinal mucosa as the main pathogenetic mechanism for the development of inflammatory diseases not only of the intestine, but also of other organs and systems, including rheumatological diseases, is being discussed.The integrity of the intestinal barrier was assessed using morphological examination of mucosal biopsies (M) of various gastrointestinal tract sections, followed by staining with hematoxylin and eosin.Electron microscopy can be used to visualize the distances between epithelial cells and the width of intercellular spaces.The analysis of the conducted studies revealed significant morphological shifts in all the studied departments of the digestive tract in rheumatological diseases, which are expressed in the treatment of infiltration of the stroma of intestinal villi by lymphocytes and plasma cells, expansion of microvessels, an increase in the number of interepithelial lymphocytes, an increase in intercellular gaps, loss of communication with the basement membrane by enterocytes, which indicates the development of SIEP in this category of patients.
Keywords: epithelial permeability; rheumatological; enterocytes